Tourism Destination Management - Rodríguez-Díaz, Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book collected studies focused on the management of tourist destinations. Destinations are complex and adaptive systems, where the different elements that make them up have to be oriented towards achieving a common objective that improves the competitiveness of the destination. Five main lines of research on tourist destinations can be established: 1) the management, planning, and marketing of destinations, with special attention to the tourism supply chain, communication, and integral management; 2) the sustainability of resources and capabilities; 3) the renewal of destinations in order to update their offer and main resources to maintain competitiveness; 4) online reputation and communication through social media in order to create and enhance a strong brand image and customer loyalty; and 5) the application of new technologies in order to develop smart destinations. The book is made up of five research studies that focus on analyzing the transition towards a more circular tourist activity in hotels, image as a competitive factor of destinations, the value of cultural creativity, the coherence of online reputation, and the relationship between hotel prices and online reputation in different tourist destinations.